2021
DOI: 10.1186/s13063-021-05273-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring new uses for existing drugs: innovative mechanisms to fund independent clinical research

Abstract: Background Finding new therapeutic uses for existing medicines could lead to safe, affordable and timely new treatment options for patients with high medical needs. However, due to a lack of economic incentives, pharmaceutical developers are rarely interested to invest in research with approved medicines, especially when they are out of basic patent or regulatory protection. Consequently, potential new uses for these medicines are mainly studied in independent clinical trials initiated and led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…In addition, the strength of second-use patents to protect against competitors is often weak ( Pushpakom et al, 2018 ; Verbaanderd et al, 2020 ). Second, additional costly clinical development investments may be needed to prove efficacy for the new indication, as well as possible additional requirements with respect to dosing and safety ( Kort & Jovinge., 2021 ; Verbaanderd et al, 2021 ). These additional costs may limit the prospects for sufficient profitability, especially when low-priced generic versions of the originator are already used off-label ( Breckenridge & Jacob., 2018 ; Verbaanderd et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the strength of second-use patents to protect against competitors is often weak ( Pushpakom et al, 2018 ; Verbaanderd et al, 2020 ). Second, additional costly clinical development investments may be needed to prove efficacy for the new indication, as well as possible additional requirements with respect to dosing and safety ( Kort & Jovinge., 2021 ; Verbaanderd et al, 2021 ). These additional costs may limit the prospects for sufficient profitability, especially when low-priced generic versions of the originator are already used off-label ( Breckenridge & Jacob., 2018 ; Verbaanderd et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative funding perspective and an altered private–public mix in the financing of R&D may bring new life to a number of compounds in different disease areas (e.g. different types of cancer, Parkinson’s disease), which are currently deprioritized because of their poor commercial prospects (Verbaanderd et al 2021 ).…”
Section: Concept Mapping and Discussionmentioning
confidence: 99%
“…In addition, study types, such as interventional or observational studies, might be different depending on the funding source, and trend changes based on study types were not observed when comparing pre- and postpandemic periods in the current analysis. Although Gresham et al reported a decline in NIH-funded trials from 2005 to 2015 [ 5 ], during the COVID-19 pandemic, government-funded medical research bodies in many countries were reported to maintain funding continuity for research studies [ 32 ]. Such an increase in the allocation of funds could influence the number of new oncology trials launched during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%